Health and well-being of refugees, asylum seekers, undocumented migrants, and internally displaced persons under COVID-19: a scoping review - El Arab, Rabie Adel; Somerville, Joel; Abuadas, Fuad H.; Rubinat-Arnaldo, Esther; Sagbakken, Mette (Frontiers in Public Health, 2023)
Objectives The objective of this scoping review was to identify what is known about the impact of COVID-19 on the physical and mental well-being of refugees, asylum seekers, undocumented migrants, and internally displaced persons. The aim was also to identify barriers influencing access to treatment or prevention. Methods The search was conducted using PubMed/Medline, CINAHL, Scopus, and ScienceDirect. A mixed methods appraisal tool was used to assess methodological rigor. The study findings were synthesized using a thematic analysis approach. Results and Discussion This review comprised 24 studies and were conducted utilizing a mixed method approach incorporating both quantitative and qualitative methodologies. Two major themes were identified related to the impact of COVID-19 on the health and wellbeing of refugees, asylum seekers, undocumented migrants, and internally displaced persons and the key barriers influencing access to treatment or prevention of COVID-19. They often have barriers to accessing healthcare due to their legal status, language barriers, and limited resources. The pandemic has further strained already limited health resources, making it even more challenging for these populations to receive healthcare. This review reveals that refugees and asylum seekers in receiving facilities face a higher risk of COVID-19 infection than the general population due to their less favorable living conditions. The various health impacts stem from a lack of access to accurate information about the pandemic, misinformation, and the exacerbation of pre-existing mental health issues caused by heightened stress, anxiety, and uncertainty, fear of deportation among undocumented migrants, and overcrowding camps and detention facilities that increase exposure risk. Social distancing measures are difficult to implement in these settings, and inadequate sanitation, hygiene, and a lack of personal protective equipment further compound the problem. Moreover, the pandemic has had significant economic consequences for these populations. Many of them rely on informal or precarious employment, which has been disproportionately affected by the pandemic. Job losses and reduced working hours, and limited access to social protection can lead to increased poverty, and food insecurity. Children faced specific challenges, such as disruptions to education, additionally, interruptions in support services for pregnant women. Some pregnant women have avoided seeking maternity care due to fears of contracting COVID-19, resulting in increased home births and delays in accessing healthcare services. Factors that play a role in vaccination reluctance include uncertainty of undocumented migrants’ inclusion in vaccination programs, furthermore, a growing vaccine hesitancy in the population; skepticism about the safety of vaccines, inadequate knowledge/education, a variety of access barriers such as language barriers, and logistical challenges including remote locations, and inaccurate information. Conclusion This review highlights that the physical health of refugees, asylum seekers, undocumented migrants, and internally displaced persons has been significantly impacted by various barriers to healthcare access during the pandemic. These barriers include legal and administrative challenges, such as a lack of documentation. Additionally, the shift to digital tools has introduced new obstacles, not only due to language barriers or limited technical knowledge but also because of structural barriers, such as the requirement of a bank ID that is often inaccessible to these groups. Other factors contributing to limited healthcare access include financial constraints, language barriers, and discrimination. Additionally, limited access to accurate information about health services, prevention measures, and available resources may hinder them from seeking care or following public health guidelines. Misinformation and lack of trust in healthcare systems can also contribute to a reluctance to access care or vaccination programs. There is concerning evidence regarding vaccine hesitancy that needs to be addressed to reduce any future pandemic outbreak, in addition there is a need to explore the factors that play a role in vaccination reluctance among children in these populations.